Control of Direct Current Motor Using Ant Colony Optimization - Soto-Gomez, J; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2016)
In this paper an Ant Colony optimization (ACO) algorithm is proposed as tuning mechanism for Proportional-Integral-Derivative(PID) controller of a direct current (DC) motor from a robotic arm. Firstly, the model of the DC motor, PID and ACO algorithm are described. Secondly, it is performed the PID tuning using Ziegler-Nichols (ZN), manual tuning and the ACO algorithm. Finally, the experimental results of PID and tuning methods are compared and discussed. © 2015 IEEE.